Analisis Profil Berpikir Relasional Peserta Didik dalam Pemecahan Masalah Kontekstual Ditinjau dari Gaya Kognitif - Nikmarocha; Dwi Juniati; Pradnyo Wijayanti (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2024)
This study aims to describe the relational thinking profile of students with field independent and field dependent cognitive styles in solving contextual problems. There are seven study groups in class VII MTsN 1 Surabaya City and two male students from class VIIA totaling 40 students were selected as subjects based on the results of the GEFT cognitive style test and equivalent mathematical ability. Students who got a GEFT score ≤ 9 were classified as field dependent (SFD) and field independent (SFI) got a score > 9. Subjects with field independent cognitive style (SFI) were selected with a score of 11, subjects with field dependent cognitive style (SFD) with a score of 7 with TKM results, namely 77 and 82. Data collection techniques in this study used TPM and interviews. Data analysis was carried out by means of data reduction, presentation and conclusion drawing. Valid data obtained through time triangulation. The results showed that in understanding the problem, (1) SFI and FFD students found important elements in a given problem. Learners SFI describes the relationship between the elements in the problem while students SFD can not explain. Learners FI and FD build relationships in determining the completion planning strategy and checking again using arithmetic operations and carrying out the plan made. Learners FI solves the problem using another method while learners FD uses the usual way. Learners FI do the recalculation while students SFD counts back by way of substitution.